Badiou Contra Badiou: Review of Alain Badiou. 2010. Five Lessons on Wagner, translated by Susan Spitzer. London: Verso - Naomi Waltham-Smith (Current Musicology, 2012)
Review of Alain Badiou, Five Lessons on Wagner